THE BATTLE OF BRITAIN AS IT REALLY WAS - Rolls Royce Magazine, Rolls Royce (Scientia Militaria - South African Journal of Military Studies, 2012)
Fifty years ago the Battle of Britain was fought in the skies over southern England, Historians have analysed the Battle in detail, and as a result some of its mystique has been torn away. For example, the RAF’s claim that 185 German aircraft were shot down on 15 September 1940 was highly inaccurate; in fact the Luftwaffe lost only about 60 bombers and fighters on that day. But there are some certainties: The Battle was Hitler’s first major reverse in the 1939-45 war, and it meant that Britain did not go the way of the countries in continental Europe which had been conquered in 1939 and in 1940 . It was a very close thing. The Royal Air Force was helped by good equipment, radar, the benefit of fighting over home territory, and German errors.